Ion Implantation Caused Defects and Their Effects on LiTaO3 Crystal Exfoliation. Issue 8 (23rd February 2022) - Zhang, Kaisheng; Luo, Wenbo; Zeng, Xiaohan; Huang, Shitian; Wan, Limin; Shuai, Yao; Wu, Chuangui; Zhang, Wanli
Abstract : Counting on its remarkable electro‐optical, pyroelectric, and piezoelectric properties, lithium tantalate (LT) has been applied in optical modulator, infrared sensors, and other devices. LT thin film with different crystal orientation is necessary for different applications and crystal ion slicing technology has fabricated single‐crystalline LT film successfully. During crystal ion slicing, the relation of defects and implantation ions is crucial for film fabrication. Comprehensive and nondestructive method is a good choice to figure out the relation and have a guide in crafting process. Z‐cut LT crystal wafers implanted with different H‐ion fluences are investigated in this research. Optical spectra, Raman spectra, and X‐ray diffraction spectra are measured, corresponding to the thermal annealing exfoliation experiment, to analyze the interactive of implantation, defects, and exfoliation. Based on the results and analysis, oxygen vacancies and H‐ion interstitials affect the crystal lattice and behave as strain increase in lattice. Strain increase contributes to the activation energy E a decrease and once the E a decreases to a limit value, exfoliation is able to happen. Depending on this analysis method, a direction to optimize exfoliation of H‐ion implanted LT has been found. Moreover, this method can also be used by optimizing crystal ion slicing technology in other materials. Abstract : Optical measurement, Raman, X‐ray diffraction (XRD) and annealing are used to characterize the defect variation in LiTaO3 implanted by H‐ion. Oxygen vacancies and H‐ion interstitials increase the strain in crystal and accelerate exfoliation. A comprehensive and nondestructive method is built to analyze the relation between implantation and exfoliation, and guide the optimization of crystal ion slicing (CIS) technology.